Chitosan-silica- polyethylene Glycol (Ch/Si/P) Solid Membrane for Removal of Cu(II), Zn(II) and Cd(II) Ions from Aqueous Solutions - Mahatmanti, F. W.; Kusumastuti, E.; Rengga, W. D. P.; Nuryono, .; Siswanta, D. (Challenges and Advances in Chemical Science Vol. 1, 2021)
Chitosan is interestingly thought to be used as raw material to make membrane for it has functional group of –NH2 and –OH that is easy to modify. Chitosan membrane has weakness like low mechanical properties. To overcome those weaknesses, silica is added on chitosan membrane synthesis to improve chitosan membrane stability. In membrane synthesis process, plasticizer is used to improve mechanical properties, maintain integrality, and avoid holes and crackness. Polyethylene Glycol plasticizer addition is expected to increase physical and mechanical properties and hydrophilic properties on membrane surface significantly therefore metal ion solution can easily diffuse through chitosan-silica-PEG membrane. In this research, it is done chitosan-silica-PEG (Ch/Si/P) membrane synthesis with tetraethyl orthosilicate (TEOS) that is used as silica source then the membrane is used as adsorbent for ion Cu(II), Zn(II) and Cd(II) by batch method. Research shows that adsorption with batch method to all membranes is optimum pH for metal ions Cu(II) and Zn(II) = 6, Cd(II) = 5.5. Adsorption for ions Cu(II), Zn(II) and Cd(II) in membrane tends to follow Langmuir isotherm model. Generally, it can be said that Ch membrane ability on all adsorption metal ions increases with silica or PEG addition. Adsorption capacity value for Ch/Si/P membrane in \(μ\)mol/g for ion Cu(II), Zn(II) and Cd(II) in order are 262, 183, and 107 \(μ\)mol/g. Generally, in adsorption kinetic data there is a tendency of coefficient score of R2 linearity that is higher in the second order of pseudo kinetic model.